Global burden of stroke in adolescents and young adults (aged 15-39 years) from 1990 to 2019: a comprehensive trend analysis based on the global burden of disease study 2019 - Zixuan Ma; Wenkai He; Yuanxin Zhou; Li Mai; Lifeng Xu; Can Li; Mingyan Li (BMC, 2024)
Summary Introduction The incidence of stroke is rising among individuals aged 15-39. Insufficient research targeting this age group hampers the development of effective strategies. This study analyzes data from the Global Burden of Disease Study 2019 (GBD 2019) to examine trends from 1990 to 2019 and propose future interventions. Methods Data on ischemic strokes, intracerebral hemorrhage, and subarachnoid hemorrhage from 1990 to 2019 was collected from the Global Health Data Exchange (GHDx) platform. We used the Annual Average Percentage Change (AAPC) to assess global trends in incidence, prevalence, Disability-Adjusted Life Years (DALYs), and mortality rates across various stroke categories. Joinpoint models identified significant years of trend inflection. Trend analyses were segmented by age, gender, and Sociodemographic Index (SDI). Findings From 1990 to 2019, the global incidence of ischemic stroke within the adolescents and young adults (AYAs) cohort declined from 1990 to 1999, further decreased from 2000 to 2009, and then increased from 2010 to 2019. The overall AAPC p-value showed no significant difference. Mortality rates for ischemic strokes were consistently reduced during this period. The overall incidence rate of intracerebral hemorrhage has exhibited a downward trend. Meanwhile, the incidence rate of subarachnoid hemorrhage decreased from 1990 to 2009, yet saw a resurgence from 2010 to 2019. Male ischemic stroke incidence grew more than female incidence, but both absolute incidence and rates were higher for females. Differences in SDI levels were observed, with the fastest increase in incidence occurring in low-middle SDI regions, followed by high SDI regions, and the smallest increase in low SDI regions. Conversely, the most rapid decline was noted in high-middle SDI regions, with no significant change observed in middle SDI regions. Conclusion A concerning trend of increasing ischemic stroke incidence, DALYs, and prevalence rates has emerged in the global 15-39 age group, especially among those aged 30-39. This increase is evident across regions with varying SDI classifications. To combat this alarming trend among adolescents and young adults, enhancing preventive efforts, promoting healthier lifestyles, strengthening the healthcare system's responsiveness, and maintaining vigilant epidemiological monitoring is essential.